2013
DOI: 10.2298/hemind120613091d
|View full text |Cite
|
Sign up to set email alerts
|

Thermo-mechanic and sensory properties of wheat and rye breads produced with varying concentration of the additive

Abstract: The effects of different concentrations of the complex additive containing emulsifiers, oxido-reductive substances and enzymes, on the rheological conditions of dough, and on the sensory properties of three groups of bread were investigated. The best initial quality and the lowest degree of protein network weakening had the dough obtained from mixed wheat and rye flours. The best expected baking properties were shown by the white wheat flour due to the least damage of its starch. The use of the additive … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…According to Menon, Swarnali & Usha (2015), the composite flours have considerably been used in making bread products to predominantly reveal functional roles of flour components and to analyze its sensory acceptability. Several authors reported negative effects of non-wheat flour (cassava, cocoyam, yam, sweet-potato, soy, maize, rye, rice) addition to wheat flour on sensory attributes in the scores for appearance, crust and crumb color, taste and flavor, which leading to a decreased overall acceptability of the composite bread (Almazan, 1990;Khalil, Mansour & Dawoud, 2000;Sabanis & Tzia, 2011;Mongi et al, 2011;Nindjin, Amani & Sindic, 2011;Rai, Kaur, Singh & Minhas, 2012;Demin et al, 2013;Bibiana, Grace & Julius, 2014;Trejo-Gonzalez, Loyo-González & Munguía-Mazariegos, 2014). Also, Kamoto, Kasapila & Tinna (2018) reported that mixing amaranth and wheat flour affects the rheological properties of dough, which, in turn, limits the baking characteristics and quality of the bread as a final product.…”
Section: Introductionmentioning
confidence: 99%
“…According to Menon, Swarnali & Usha (2015), the composite flours have considerably been used in making bread products to predominantly reveal functional roles of flour components and to analyze its sensory acceptability. Several authors reported negative effects of non-wheat flour (cassava, cocoyam, yam, sweet-potato, soy, maize, rye, rice) addition to wheat flour on sensory attributes in the scores for appearance, crust and crumb color, taste and flavor, which leading to a decreased overall acceptability of the composite bread (Almazan, 1990;Khalil, Mansour & Dawoud, 2000;Sabanis & Tzia, 2011;Mongi et al, 2011;Nindjin, Amani & Sindic, 2011;Rai, Kaur, Singh & Minhas, 2012;Demin et al, 2013;Bibiana, Grace & Julius, 2014;Trejo-Gonzalez, Loyo-González & Munguía-Mazariegos, 2014). Also, Kamoto, Kasapila & Tinna (2018) reported that mixing amaranth and wheat flour affects the rheological properties of dough, which, in turn, limits the baking characteristics and quality of the bread as a final product.…”
Section: Introductionmentioning
confidence: 99%
“…Mandatory ingredients which involve in bread making are: flour, yeast and water, additional raw materials are: sugar, Original research paper UDK 664.661/.663:577.164.2:664.1]:543.92 DOI 10.5937/ffr48-34944 fat, milk, etc. and improvers such as: different types of additives and emulsifier (Demin et al, 2013;Umelo et al, 2014). In recent years, numerous studies were conducted to improve bread nutritional value (macronutrients: carbohydrates, proteins, fat and dietary fibres; micronutrients: minerals and vitamins), health supporting bioactive compounds, sensory acceptability, shelf life and to match its affordability.…”
Section: Introductionmentioning
confidence: 99%
“…According to Menon, Swarnali & Usha (2015), the composite flours have considerably been used in making bread products to predominantly reveal functional roles of flour components and to analyze its sensory acceptability. Several authors reported negative effects of non-wheat flour (cassava, cocoyam, yam, sweet-potato, soy, maize, rye, rice) addition to wheat flour on sensory attributes in the scores for appearance, crust and crumb color, taste and flavor, which leading to a decreased overall acceptability of the composite bread (Almazan, 1990;Khalil, Mansour & Dawoud, 2000;Sabanis & Tzia, 2011;Mongi et al, 2011;Nindjin, Amani & Sindic, 2011;Rai, Kaur, Singh & Minhas, 2012;Demin et al, 2013;Bibiana, Grace & Julius, 2014;Trejo-Gonzalez, Loyo-González & Munguía-Mazariegos, 2014). Also, Kamoto, Kasapila & Tinna (2018) reported that mixing amaranth and wheat flour affects the rheological properties of dough, which, in turn, limits the baking characteristics and quality of the bread as a final product.…”
Section: Introductionmentioning
confidence: 99%